Problems faced by Port Dickson Beach Club Resort: focusing on the effectiveness of services management / Norashikin Zakaria - Zakaria, Norashikin (Faculty of Business and Management, 2006)
The purpose of this study is to find out the important determinant that can improve the effectiveness of services management at PDSCR. Understanding the problem faced by POSCR is important to solve the problems of services management. Customer and the employee at POSCR are involved in this research.